Public Order, Public Protest and Public Monuments - Hare, Ivan (Victoria University of Wellington Law Review, 2023)
Much public protest in recent years has been directed towards monuments to controversial figures who have profited from the slave trade or other exploitative activities. The most striking example in the United Kingdom has been the fate of the four individuals accused of damaging the statue to Edward Colston in Bristol as part of a Black Lives Matter demonstration. This article examines the arguments relied on by the defence at trial and in the Attorney-General’s Reference which followed their acquittal. The article begins by setting protest relating to public monuments in its international and historical context.